Effect of Pyriproxyfen, a Malaria Vector Larvicide, on the Growth and Mortality of Vannamei Shrimp - Putri, Sriana; Setyaningrum, Endah; Farisi, Salman (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2023)
Anopheles mosquito shared a breeding site with the vannamei shrimp (Litopenaeus vannamei). Anopheles mosquito larvae commonly live in both stagnant fresh and brackish water. The potential breeding habitat of Anopheles mosquito larvae may be rice fields, pools or ponds, swamps, ditches, and slow-current streams. One of the effective strategies to control malaria is to apply chemical insecticides. Pyriproxifen is a larvicide that contains juvenile hormone-like compounds. Juvenile hormone-like compounds can affect mosquito morphogenesis, characterized by the failure of the larvae to develop into pupae. With a completely randomized design, the shrimp fry was divided into 4 groups, 6 repetitions, 20 individuals each. Shrimp fry in each experimental unit was placed and maintained in plastic jars containing 2.5 L of brackish water. The results showed that the insect growth regulator (IGR) with the active ingredient pyriproxyfen at various concentrations had no significant effect on the growth, mortality, and survival of vannamei shrimp fry. It can be concluded therefore that pyriproxifen larvicide was safe to be used for controlling malaria mosquito vectors in hatcheries and breeding ponds of vannamei shrimp.